Patterns of adverse childhood experiences and cardiovascular risk factors in U.S. adults. (4th June 2022) - Wooldridge, Jennalee S.; Tynan, Mara; Rossi, Fernanda S.; Gasperi, Marianna; McLean, Caitlin L.; Bosch, Jeane; Trivedi, Ranak B.; Herbert, Matthew S.; Afari, Niloofar
Abstract: Adverse Childhood Experiences (ACEs) are associated with poor health yet, we know little about how distinct patterns of ACE types are associated with cardiovascular (cardiovascular (CVD)) risk factors. The current study 1) examined associations of latent ACE classes with modifiable CVD risk factors including high cholesterol, smoking, diabetes, hypertension, high triglycerides, physical inactivity, overweight/obesity, and lifetime depression; and 2) examined the impact of socioeconomic status‐related (SES) factors on these relationships. Using a cross‐sectional analysis of the National Epidemiologic Survey of Alcohol and Related Conditions‐III ( n  = 36, 309) data, four latent classes of ACEs were previously identified: 1) low adversity, 2) primarily household dysfunction, 3) primarily maltreatment, and 4) multiple adversity types. We examined the association of these classes with CVD risk factors in adulthood and subsequently, the same model accounting for SES‐related factors. Tobacco smoking, overweight/obesity, and lifetime depression were each associated with higher odds of being in classes 2, 3, and 4 than class 1, respectively. These relationships held after adjusting for SES‐related factors. Class 4 was associated with the most CVD risk factors, including high triglycerides and high cholesterol after controlling for SES‐related factors. The consistent associations between tobacco smoking, overweight/obesity, and lifetime depression with each adverse ACE profile, even after controlling for SES, suggest behavioural CVD prevention programs should target these CVD risk factors simultaneously.